Theology in the Shadow of the Holocaust: Revisiting Bonhoeffer and the Jews. Issue 2 (July 2022) - Braverman, Mark
The scholarship on Dietrich Bonhoeffer and the Jews has focused on two questions: (1) To what extent did the persecution of the Jews drive Bonhoeffer's actions with respect to the Third Reich, and (2) Did Bonhoeffer's theology of Judaism and the Jewish people undergo a change as a result of the Nazi program of persecution and extermination? The work ranges from writers who reject the hagiography of a Bonhoeffer who for the sake of the Jews joined the resistance and paid the ultimate price, to those who argue that the persecution of the Jews was key in the development of Bonhoeffer's theology and his resistance to National Socialism. Bonhoeffer biographer Eberhard Bethge figured large in this second group; Bethge's work in this area coincided with his involvement in Christian post-Holocaust theology, an expression of the intensely philojudaic theology that emerged in the West following World War II. Driven by the desire to atone for millennia of anti-Jewish doctrine and action, post-Holocaust theology has exerted a strong influence on Bonhoeffer scholarship. The argument of this article is that the postwar focus on Christian anti-Judaism has led the church away from confronting the exceptionalism that persists in Christian identity and teaching. In its penitential zeal, the postwar project to renounce church anti-Judaism has instead replaced it with a Judeo-Christian triumphalism and a theological embrace of political Zionism that betray fundamental gospel principles. These run counter to the passionate opposition to the merger of hyper-nationalism and religion that informs Bonhoeffer's radical, humanistic Christology. Fashioning Bonhoeffer as a martyr for the Jews and as a forerunner of post-Holocaust theology does damage to the legacy of his theology and distorts the lessons of his life and witness. This carries implications for the role of the church in confronting the urgent issues of our time.